Isolation and characterization of dihydropteridine reductase from Pseudomonas species. - Williams, C D (1976)
Dihydropteridine reductase isolated from the bacterium Pseudomonas species (ATCC 11299a) has been purified approximately 450-fold byammonium sulfate precipitation and diethylaminoethyl-cellulose chromatographic procedures. The preparation is at least 80% pure as judged by polyacrylamide gels. Its molecular weight was determined to be about 44,000. Both dihydropteridine reductase and phenylalanine hydroxylase activities were found to be higher in cells adapted to a medium containing L-phenylalanine or L-tyrosine as the sole carbon source than in those grown in L-asparagine. The substrate of the reductase is quinonoid dihydropteridine, and the product is tentatively identified as a tetrahydropteridine through its ability to serve as a cofactor for phenylalanine hydroxylase. The enzyme shows no marked specificity for the pteridine cofactor that occurs naturally in this organism, L-threo-neopterin. The pH optimum for the reductase is 7.2, and nicotinamide adenine dinucleotide, reduced form, is the preferred cosubstrate. Inhibition of the reduced and untreated enzyme by several sulfhydryl reagents was observed. A metal requirement for the reductase could not be demonstrated. Dihydropteridine reductase was found to be inhibited by aminopterin in a competitive manner with respect to the quinonoid dihydro form of 2-amino-4-hydroxy-6,7-dimethyl-5,6,7,8-tetrahydropteridine.